A novel class of rigid-rod perylene diimides and isoindigo semiconducting polymers. Issue 4 (22nd December 2021) - Yu, Yaping; Zhu, Danlei; Zhu, Xiuyuan; Ravva, Mahesh Kumar; Duan, Jiayao; Jiang, Lang; Li, Zhengke; Yue, Wan
Abstract : Three novel rigid-rod semiconducting polymers containing fused electron-deficient PDI and IID units have been synthesized through aldol polymerization. Their unique opto-electronic properties have been investigated systematically. Abstract : Rigid-rod conjugated polymers contain only double-bond linkers instead of single bonds between the monomer linkages along the backbone. These polymers exhibit exceptional optoelectronic properties and promising device performances owing to their unique structures. Yet, such polymers are still very limited and little is known about their structure–property relationship so far. Herein, we have designed and synthesized a series of novel rigid-rod semiconducting polymers containing fused electron-deficient perylene diimides and isoindigo units through an inexpensive and high atom-economy method. Furthermore, the acid-mediated aldol condensation reactions do not involve any toxic reagents or transition metal catalysts. Most importantly, these polymers are isomerically pure unlike previously reported PDI polymers. The energy levels and optoelectronic properties of these polymers are tuned via adopting a molecular strategy of acene size optimization and heteroatom substitution on the variable lactone or lactams. All electron-deficient character endowed them with low-lying LUMOs, and electron transport in solution-processed thin film transistor devices has been realized using two of the polymers. Therefore the rigid-rod and fused semiconducting polymers reported here extend the scope of aldol polymerization and provide a remarkable platform for fundamental optoelectronic investigations and material innovation in the area of organic (bio)electronics.